Can Melatonin Act as an Antioxidant in Hydrogen Peroxide-Induced Oxidative Stress Model in Human Peripheral Blood Mononuclear Cells?. (11th January 2016) - Emamgholipour, Solaleh; Hossein-Nezhad, Arash; Ansari, Mohammad
Abstract : Purpose. We aimed to investigate the possible effects of melatonin on gene expressions and activities of MnSOD and catalase under conditions of oxidative stress induced by hydrogen peroxide (H2 O2 ) in peripheral blood mononuclear cells (PBMCs). Materials and Methods. PBMCs were isolated from healthy subjects and treated as follows: (1) control (only with 0.1% DMSO for 12 h); (2) melatonin (1 mM) for 12 h; (3) H2 O2 (250  μ M) for 2 h; (4) H2 O2 (250  μ M) for 2 h following 10 h pretreatment with melatonin (1 mM). The gene expression was evaluated by real-time PCR. MnSOD and catalase activities in PBMCs were determined by colorimetric assays. Results. Pretreatment of PBMCs with melatonin significantly augmented expression and activity of MnSOD which were diminished by H2 O2 . Melatonin treatment of PBMCs caused a significant upregulation of catalase by almost 2-fold in comparison with untreated cells. However, activity and expression of catalase increased by 1.5-fold in PBMCs under H2 O2 -induced oxidative stress compared with untreated cell. Moreover, pretreatment of PBMCs with melatonin resulted in a significant 1.8-fold increase in catalase expression compared to PBMCs treated only with H2 O2 . Conclusion. It seems that melatonin could prevent from undesirable impacts of H2 O2 -induced oxidative stress on MnSOD downregulation. Moreover, melatonin could promote inductive effect of H2 O2 on catalase mRNA expression.